Characterization of Phrenic Nerve Response to Pulsed Field Ablation. (1st June 2022) - Howard, Brian; Haines, David E.; Verma, Atul; Kirchhof, Nicole; Barka, Noah; Onal, Birce; Stewart, Mark T.; Sigg, Daniel C.
Abstract : Background: Phrenic nerve palsy is a well-known complication of cardiac ablation, resulting from the application of direct thermal energy. Emerging pulsed field ablation (PFA) may reduce the risk of phrenic nerve injury but has not been well characterized. Methods: Accelerometers and continuous pacing were used during PFA deliveries in a porcine model. Acute dose response was established in a first experimental phase with ascending PFA intensity delivered to the phrenic nerve (n=12). In a second phase, nerves were targeted with a single ablation level to observe the effect of repetitive ablations on nerve function (n=4). A third chronic phase characterized assessed histopathology of nerves adjacent to ablated cardiac tissue (n=6). Results: Acutely, we observed a dose-dependent response in phrenic nerve function including reversible stunning (R 2 =0.965, P <0.001). Furthermore, acute results demonstrated that phrenic nerve function responded to varying levels of PFA and catheter proximity placements, resulting in either: no effect, effect, or stunning. In the chronic study phase, successful isolation of superior vena cava at a dose not predicted to cause phrenic nerve dysfunction was associated with normal phrenic nerve function and normal phrenic nerve histopathology at 4 weeks. Conclusions: Proximity of the catheter to the phrenic nerve and the PFA dose level were critical for phrenic nerve response. Gross and histopathologic evaluation of phrenic nerves and diaphragms at a chronic time point yielded no injury. These results provide a basis for understanding the susceptibility and recovery of phrenic nerves in response to PFA and a need for appropriate caution in moving beyond animal models.